The Effect of Price Perception, Product Quality and Brand Image on Purchase Decisions For Adidas Shoe Products - Fathan Afiq Juhaida; Istiqomah Istiqomah; Sarsono Sarsono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of price perception, product quality, and brand image on purchasing decisions for Adidas shoes at Solo Paragon Mall, Surakarta. This study uses a quantitative approach with a causal associative research type. The sampling technique uses purposive sampling with a total of 100 respondents. The data analysis method used is multiple linear regression with the help of the SPSS 21.0 program. The results of the study indicate that simultaneously, price perception, product quality, and brand image have a significant effect on purchasing decisions with an F-value of 50.787 and a significance of 0.000. Partially, the three independent variables also have a significant effect on purchasing decisions, where price perception has a significance value of 0.042, product quality 0.010, and brand image 0.000. The coefficient of determination (Adjusted R²) value of 0.601 indicates that 60.1% of the variation in purchasing decisions can be explained by these three variables, while the remaining 39.9% is influenced by other factors outside the study. Thus, brand image is the most dominant variable influencing purchasing decisions, followed by product quality and price perception. Keywords: Price Perception, Product Quality, Brand Image, Purchase Decision